Investigation of a measles outbreak in Cordillera, Northern Philippines, 2013 - Ching, Paola Katrina; Zapanta, Ma Justina; de los Reyes, Vikki Carr; Tayag, Enrique; Magpantay, Rio (Western Pacific Surveillance and Response, 2016)
Introduction: Measles is a highly infectious viral illness that remains one of the leading causes of death among children worldwide. In the Philippines, decreasing routine vaccination coverage from 2007 to 2011 led to local measles outbreaks. A team investigated a measles outbreak reported in Cordillera of the Philippines in May 2013. Methods: Measles case data with symptom onset from 2 February to 27 May 2013 were obtained from official sources and verified on site. Data included age, sex, residential address, signs and symptoms and vaccination status. Active case-findings were also conducted for contacts of these cases. The living environments of the cases were investigated. A survey was conducted with the cases and caregivers to understand their knowledge and attitudes about measles. Results: There were 50 measles cases identified with an age range from six months to 32 years (median: 16 years). Thirty-two were male (64%). Twenty (40%) were hospitalized with one death. Thirty-two (64%) cases were laboratory confirmed, and 36 (72%) received a single dose of measles vaccine. Overcrowded living environments were observed among many cases. The majority of respondents (46/48, 96%) knew about measles, but there were misconceptions about the cause of measles and how it can be prevented and managed. Conclusion: This measles outbreak occurred in an area with low immunization coverage. Achieving 95% measles immunization coverage and strengthening routine immunization strategies to address high-risk populations are recommended. Also, we recommend health education campaigns to include components that address misconceptions about measles.